N6-methyladenosine modification: A potential regulatory mechanism in spinal cord injury - Liu, Derong; Fan, Baoyou; Li, Jinze; Sun, Tao; Ma, Jun; Zhou, Xianhu; Feng, Shiqing (Frontiers in Cellular Neuroscience, 2022)
N6-methyladenosine (m6A), an essential post-transcriptional modification in eukaryotes, is closely related to the development of pathological processes in neurological diseases. Notably, spinal cord injury (SCI) is a serious traumatic disease of the central nervous system, with a complex pathological mechanism which is still not completely understood. Recent studies have found that m6A modification levels are changed after SCI, and m6A-related regulators are involved in the changes of the local spinal cord microenvironment after injury. However, research on the role of m6A modification in SCI is still in the early stages. This review discusses the latest progress in the dynamic regulation of m6A modification, including methyltransferases (“writers”), demethylases (“erasers”) and m6A -binding proteins (“readers”). And then analyzes the pathological mechanism relationship between m6A and the microenvironment after SCI. The biological processes involved included cell death, axon regeneration, and scar formation, which provides new insight for future research on the role of m6A modification in SCI and the clinical transformation of strategies for promoting recovery of spinal cord function.